2015
DOI: 10.1097/ccm.0000000000001015
|View full text |Cite
|
Sign up to set email alerts
|

Patient Mortality Is Associated With Staff Resources and Workload in the ICU

Abstract: This study proposes evidence-based thresholds for patient-to-caregiver ratios, above which patient safety may be endangered in the ICU. Real-time monitoring of staffing levels and workload is feasible for adjusting caregivers' resources to patients' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
175
3
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(198 citation statements)
references
References 30 publications
(30 reference statements)
6
175
3
8
Order By: Relevance
“…YBÜ'de izlenen kritik hastalarda monitörizasyon, ilaç uygulamaları ve girişimler nitelik ve niceliksel olarak oldukça fazladır ve tüm bu nedenlerden dolayı verilmekte olan hemşirelik hizmeti sağ kalımı doğrudan etkileyebilmektedir (1,2). Ayrıca maliyetler göz önüne alındığında kaynakların etkin olarak kullanılması amacı ile YBÜ'de izlenmesi gereken hastaların tanımlanması, hasta gruplarına ve hastalık şiddetlerine paralel olarak oluşacak hemşire iş yükünün belirlenmesi ve ünitenin organizasyonundaki planlamalarının bu değerlendirmeler ışığında yapılması gereklidir.…”
Section: Introductionunclassified
“…YBÜ'de izlenen kritik hastalarda monitörizasyon, ilaç uygulamaları ve girişimler nitelik ve niceliksel olarak oldukça fazladır ve tüm bu nedenlerden dolayı verilmekte olan hemşirelik hizmeti sağ kalımı doğrudan etkileyebilmektedir (1,2). Ayrıca maliyetler göz önüne alındığında kaynakların etkin olarak kullanılması amacı ile YBÜ'de izlenmesi gereken hastaların tanımlanması, hasta gruplarına ve hastalık şiddetlerine paralel olarak oluşacak hemşire iş yükünün belirlenmesi ve ünitenin organizasyonundaki planlamalarının bu değerlendirmeler ışığında yapılması gereklidir.…”
Section: Introductionunclassified
“…In this sample, the extremes are represented by ICUs in the United Kingdom, where 97% reported a 1:1 nurse/patient ratio, in contrast to French ICUs, with 90% reporting 1:3 or higher nurse/patient ratios (including 66% with a ratio of 1:4). Many studies have shown that heavier nursing workloads are associated with poor patient outcomes (29). Specifically, one meta-analysis of 90 studies found that increased registered nurse staffing was associated with lower mortality in intensive care, medical, and surgical units; reduced risk of hospital-acquired pneumonia, unplanned extubation, respiratory failure, cardiac arrest, and failure to rescue; and shorter lengths of stay for both surgical and ICU patients (30).…”
Section: Original Researchmentioning
confidence: 99%
“…8 Reinforcing the rationale for identifying and studying staff dimensioning, it is known that, at the international level, the high workload of the nursing team -commonly associated with the quantitative deficit of professionals -can directly compromise the care quality. It can contribute, for example, to a higher risk of death with the reduction of the proportion of nurses per patient, 9 increased rates of adverse events, such as pressure injuries, falls, errors in drug administration 10 and hospital infections, and increased length of hospitalization.…”
mentioning
confidence: 99%